Vaccine formulations in clinical development for the prevention of severe acute respiratory syndrome coronavirus 2 infection - Batty, Cole J. (Adv Drug Deliv Rev, 2021)
The COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to an unprecedented effort toward the development of an effective and safe vaccine. Aided by extensive research efforts into characterizing and developing countermeasures towards prior coronavirus epidemics, as well as recent developments of diverse vaccine platform technologies, hundreds of vaccine candidates using dozens of delivery vehicles and routes have been proposed and evaluated preclinically. A high demand coupled with massive effort from researchers has led to the advancement of at least 31 candidate vaccines in clinical trials, many using platforms that have never before been approved for use in humans. This review will address the approach and requirements for a successful vaccine against SARS-CoV-2, the background of the myriad of vaccine platforms currently in clinical trials for COVID-19 prevention, and a summary of the present results of those trials. It concludes with a perspective on formulation problems which remain to be addressed in COVID-19 vaccine development and antigens or adjuvants which may be worth further investigation.